Assessment of bilateral asymmetry in cycling using a commercial instrumented crank system and instrumented pedals - Bini, R. R.; Hume, P. A. (International Journal of Sports Physiology and Performance, 2014)
The accuracy of commercial instrumented crank systems for symmetry assessment in cycling has not been fully explored. Therefore, the authors` aims were to compare peak crank torque between a commercial instrumented crank system and instrumented pedals and to assess the effect of power output on bilateral asymmetries during cycling. Ten competitive cyclists performed an incremental cycling test to exhaustion. Forces and pedal angles were recorded using right and left instrumented pedals synchronized with crank-torque measurements using an instrumented crank system. Differences in right (dominant) and left (nondominant) peak torque and asymmetry index were assessed using effect sizes. In the 100- to 250-W power-output range, the instrumented pedal system recorded larger peak torque (dominant 55-122%, nondominant 23-99%) than the instrumented crank system. There was an increase in differences between dominant and nondominant crank torque as power output increased using the instrumented crank system (7% to 33%) and the instrumented pedals (9% to 66%). Lower-limb asymmetries in peak torque increased at higher power-output levels in favor of the dominant leg. Limitations in design of the instrumented crank system may preclude the use of this system to assess peak crank-torque symmetry.